Lyle Creelman : the frontiers of global nursing - Armstrong-Reid, Susan, 1950- (University of Toronto Press, 2014)
In telling Creelman's fascinating story, Susan Armstrong-Reid helps readers learn about the transformation of the nursing profession and global health governance in the twentieth century.